Послання як засіб релігійної комунікації - Тарасюк, Тетяна; Tarasiuk, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано специфіку релігійної комунікації, особливості конструювання комунікативного акту посередництвом сучасних релігійних послань. Основну увагу акцентовано на способах репрезентації послань та ролі передавача та інтерпретатора цього типу тексту. The article presents the analysis of religious communication specificity, peculiarities of communicative act construction with the help of contemporary religious epistles. The main structuralsemantic characteristics of this type of text are highlighted. The primary attention is drawn to the means of epistles’ representations, the role of the sender and the recipient of this text type. The differential features of verbal and written form of epistle transmission are defined. The factors which are supporting (or vice versa – inhibiting) the effectiveness of such means of religious communication are determined.
Epistle as Means of Religious Communication
Keywords: релігійне послання; комунікація; комунікативний акт; адресант; передавач; адресат; religious epistle; communication; communicative act; addresser; addressee; sender